PERBEDAAN MODEL PEMBELAJARAN PROJECT BASED LEARNING DAN BERPIKIR KRITIS TERHADAP HASIL BELAJAR SISWA KELAS X SMAN 1 PERCUT PADA MATA PELAJARAN EKONOMI - Sernanda Putri Darma (Smart Education, 2026)
Abstract: This study aims to determine the differences in economics learning outcomes between students taught using the Project Based Learning (PjBL) model and those taught using conventional learning, to identify differences in learning outcomes based on students' critical thinking skills, and to examine the interaction between learning models and critical thinking skills on students' economics learning outcomes. This research employed a quantitative approach with a quasi-experimental design. The sample consisted of 72 students, including 36 students in the experimental class and 36 students in the control class. Data were collected through learning outcome tests and critical thinking skill tests. Data analysis was conducted using descriptive statistics, normality tests, homogeneity tests, N-Gain tests, and Independent Sample t-Tests. The results showed significant differences in economics learning outcomes between students taught using Project Based Learning and conventional learning. The mean posttest score of the experimental class was 85.97, higher than the control class score of 55.14. The t-test result showed a t-value of 14.805 with a significance value of 0.000 < 0.05. The average N-Gain score of the experimental class was 0.7058 (high category), while the control class obtained 0.1733 (low category). The findings also indicate that critical thinking skills contribute to improving students' learning outcomes. Therefore, Project Based Learning is effective in enhancing economics learning outcomes and students' critical thinking skills. Keywords: Project Based Learning, Critical Thinking Skills, Economics Learning Outcomes. Abstrak: Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar ekonomi antara siswa yang diajar menggunakan model Project Based Learning (PjBL) dan pembelajaran konvensional, mengetahui perbedaan hasil belajar berdasarkan kemampuan berpikir kritis siswa, serta mengetahui interaksi antara model pembelajaran dan kemampuan berpikir kritis terhadap hasil belajar ekonomi siswa. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian quasi experiment. Sampel penelitian berjumlah 72 siswa yang terdiri dari 36 siswa kelas eksperimen dan 36 siswa kelas kontrol. Teknik pengumpulan data menggunakan tes hasil belajar dan tes kemampuan berpikir kritis. Analisis data dilakukan menggunakan statistik deskriptif, uji normalitas, uji homogenitas, uji N-Gain, dan Independent Sample t-Test. Hasil penelitian menunjukkan bahwa terdapat perbedaan hasil belajar ekonomi antara siswa yang diajar menggunakan model Project Based Learning dan pembelajaran konvensional. Nilai rata-rata posttest kelas eksperimen sebesar 85,97 lebih tinggi dibandingkan kelas kontrol sebesar 55,14. Hasil uji t menunjukkan nilai t hitung sebesar 14,805 dengan signifikansi 0,000 < 0,05. Rata-rata N-Gain kelas eksperimen sebesar 0,7058 (kategori tinggi), sedangkan kelas kontrol sebesar 0,1733 (kategori rendah). Hasil penelitian juga menunjukkan bahwa kemampuan berpikir kritis berperan dalam meningkatkan hasil belajar siswa. Dengan demikian, model Project Based Learning efektif digunakan untuk meningkatkan hasil belajar ekonomi dan kemampuan berpikir kritis siswa. Kata kunci: Project Based Learning, berpikir kritis, hasil belajar ekonomi.